1996
DOI: 10.1016/s0022-5223(96)70019-3
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension after operations for congenital heart disease: Analysis of risk factors and management

Abstract: Mixed venous saturation monitoring and alpha-receptor blockade reduced the incidence of pulmonary hypertension after operations for congenital heart disease. Early definitive repair reduced morbidity and mortality from postoperative pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 15 publications
1
104
3
6
Order By: Relevance
“…Concurrently with this better understanding of the development of pulmonary hypertension, there has been a trend toward early surgical repair in neonates and infants with congenital heart disease with significant left to right shunt, even among premature and low-birth-weight neonates (13,14,39,51). Despite improved outcomes compared with initial palliation and delayed repair, Bando et al (5) have found that preexisting pulmonary hypertension and "late repair" continued to be significant risk factors for perioperative morbidity and mortality. The aim of our study was to determine the effect of increased pulmonary blood flow on SP-A, -B, and -C gene expressions in a lamb model of congenital heart disease with significant left to right shunt within the first week of life.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently with this better understanding of the development of pulmonary hypertension, there has been a trend toward early surgical repair in neonates and infants with congenital heart disease with significant left to right shunt, even among premature and low-birth-weight neonates (13,14,39,51). Despite improved outcomes compared with initial palliation and delayed repair, Bando et al (5) have found that preexisting pulmonary hypertension and "late repair" continued to be significant risk factors for perioperative morbidity and mortality. The aim of our study was to determine the effect of increased pulmonary blood flow on SP-A, -B, and -C gene expressions in a lamb model of congenital heart disease with significant left to right shunt within the first week of life.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with elevated pulmonary arterial pressure preoperatively are at higher risk of developing postoperative PAH. 29,30 Advanced PAH therapies might have the potential to produce a reduction in pulmonary vascular resistance, lowering perioperative risks and possibly widening the range of cases amenable to repair.…”
Section: Corrective Interventionsmentioning
confidence: 99%
“…Since inhaled nitric oxide (iNO) is established as an additional therapeutic option, the mortality rate of PAH has further declined. [4,18,19,20] Despite relatively high mortality rates reported in the literature, two deaths occur in our study population. However, this finding should be confirmed in further large-scale studies, before we conclude that the use of aerosolized iloprost reduces the mortality rates.…”
Section: Discussionmentioning
confidence: 56%